Crystals, crystals everywhere but not a clue till late... Light chain crystalline proximal tubulopathy with concomitant myeloma cast nephropathy - Smita Mary Matthai; Suceena Alexander; Shibu Jacob; Neelaveni Duhli; Vinoi George David; Santosh Varughese (Wolters Kluwer Medknow Publications, 2020)
The renal diseases commonly associated with myeloma include primary amyloidosis, cast nephropathy, and light chain deposition disease. Less frequent forms of renal involvement encountered in the course of myeloma are crystalline and non-crystalline proximal tubulopathies, neoplastic plasma cell infiltration, and immunoglobulin crystallization in interstitial histiocytes and glomerular cells including podocytes. Light chain proximal tubulopathy (LCPT) caused by aggregation of non-crystalline and rarely crystalline deposits of monoclonal light chains in the cytoplasm of proximal tubular epithelial cells, accounts for less than 5% of monoclonal gammopathy-associated kidney diseases. We report the case of a 48-year-old Indian woman with multiple myeloma, who presented with acute kidney injury and nephrotic syndrome, in whom the renal biopsy revealed widespread crystalline inclusions in extraglomerular and glomerular compartments. We present illustrative light microscopic (LM) and diagnostic electron microscopic (EM) findings of this case which enabled a diagnosis of crystalline LCPT, crystal storing histiocytosis, and crystalline podocytopathy occurring synchronously with myeloma cast nephropathy. While documenting this unique juxtapositioning of multicompartmental paraproteinemic renal injury in multiple myeloma, diagnosed after EM analysis of the patient's renal biopsy, we discuss the pathogenetic pathways of this condition along with the clinical implications. Due to intrinsic structural properties of the crystals, they frequently escape detection by routine LM, necessitating EM analysis for their diagnosis. Given the prognostic implications of tubulopathies complicating myeloma, LCPT is a critically important diagnosis, highlighting the need for a comprehensive renal biopsy evaluation inclusive of EM for the practice of precision medicine in such scenarios.